Attitudes of key professionals towards people with intellectual disabilities and their inclusion in society: A qualitative study in an Indonesian context. (June 2021) - Tri Handoyo, Restu; Ali, Afia; Scior, Katrina; Hassiotis, Angela
This study aimed to explore key professionals' attitudes towards people with intellectual disability (ID) and inclusion of said people in the community. Eighteen participants from three professional groups, comprising health practitioners (medical doctors, psychologists), mainstream/special education teachers, and religious leaders (Islam, Catholicism, Protestantism, Hinduism, and Buddhism) were recruited. Semistructured interviews, aided by two vignettes depicting mild and severe ID, were conducted. Thematic analysis was used to analyse the data. Seven themes were identified exploring: perceived causes; use of terminology; attitudes towards people with ID; attitudes towards inclusion, religion and ID; family-centric support; and challenges faced by people with ID in a wider context. Perceived capabilities of persons with ID were found to influence attitudes towards people with ID and their inclusion. Availability and accessibility of good quality services were also found to influence attitudes towards the inclusion of people with ID. Cultural factors related to attitudes towards ID are discussed.